Siamese ghost(s), the Doppelgänger in Twin Peaks. Issue 4 (4th July 2021) - Peters, Luc
ABSTRACT: Ghosts shape organization. The problem with this is that ghosts have a tendency to hide from our perception. This means that it is difficult to perceive the way organization is shaped. A different way to get some idea of the way they behave is through the use of film as art. An example is Twin Peaks and the way in which it reveals ghosts and the way these shape organization. In this, a special position is taken by the Doppelgänger, that is the one and the other and especially what is in-between. In this paper, the concept of the Doppelgänger and the way it is displayed in Twin Peaks is investigated. This will inform us on the unveiling of the way ghosts behave in organization.